Legal Implications of Artificial Intelligence (AI) as a Legal Subject on Intellectual Property Rights - Rahma Fatmawati; Irma Mangar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
The purpose of the study is to find out that AI is a form rather than a legal subject and provides legal certainty for each user, as well as the extent of the legality of the use of AI in creating an scientific work with conceptual and challenges to AI regulation in Indonesia. Artificial Intelligence is a computer system designed to perform tasks that are usually performed by humans and that require human intelligence. many assume that this AI is an artificial robot. this happens because of the many animations in a film or story on television, social media or written media that illustrate that this AI is an artificial robot that is described as resembling a human. this study uses legal research with a normative approach method, with the problem of whether AI can be said to be a legal subject on intellectual property rights and if AI is able to create a product or work whether the creation can be said to be a right to ownership. this is in line with research on the era of artificial intelligence and the impact on human dignity in ethical studies that ethically examine the problem of AI in discovery with humans as developers, users, and objects in this day and age, especially the impact on human dignity. of course, it is a comparative material in conducting research, in this case this article focuses on the position and subject of law on artificial intelligence.